The Effect of Alachlor-Atrazine Mixture and Diuron On Weed Control, Growth and Yield of Maize And Their Residual Effect On Growth, Nodulation and Yield of Cowpea. - Acquaye, C.A. (University of Ghana, 1995)
Two field experiments were carried out from July 1993 to January 1994 at the University of Ghana farm, Legon. The first experiment investigated the effects of two preemergent herbicides alachlor-atrazine mixture and diuron at the manufacturers' recommended rates and at rates 50% above those recommended on weed control, growth and yield of maize variety 'Abeleehi'. The second experiment carried out on the same plots determined the residual effects of these herbicides on two varieties of cowpea 'Asontem' and 'Bengpla'. At the two rates rate of 51/ha (1.8kg + 1.0kg ai/ha) and 71/ha (2.5kg + 1.4kg ai/ha) for alachlor and atrazine mixture and 1.12kg/ha (0.9kg ai/ha) and 1.68kg/ha (1.3kg ai/ha) for diuron investigated both broad-leaved weeds and grasses were controlled efficiently in maize, although the effectiveness of the chemical weed control did not differ significantly from the hand-weeding method. With regards to their influence on the growth and development of maize plants, alachlor-atrazine mixture was tolerated better by the plants than diuron. Highest grain yield was recorded on plots treated with alachlor-atrazine mixture at the manufacturer's recommendation of 1.8kg + 1.0kg ai/ha. Increases in the concentration of both herbicides were toxic to the maize. Diuron had a significantly adverse carry over effect on the succeeding cowpea crops, resulting in very low yields. Alachlor-atrazine mixture at the two rates applied which may otherwise be toxic to cowpea appeared degraded from plots by the time of the second cropping, approximately fourteen weeks after application since there were no significant adverse effects on cowpea crops. Although there appeared not to have been a differential response in the influence of the residual effect of the herbicides on the growth of cowpeas, varietal differences were detected for some of the characters investigated. Overall 'Asontem' emerged a better succeeding crop with maize in which alachlor-atrazine mixture at the manufacturer's recommended rate had been employed for weed control. Inspite of its relative unsuitability for weed control in maize in this study, it was suggested that diuron at rates lower than the manufacturer's recommended could be tested to ascertain the usefulness of this herbicide for adequate weed control without injury to maize plants before ruling it out as one of the choices of herbicides for weed control in maize.
Thesis (MPhil.) - University of Ghana, 1995
Keywords: Weed Control; Weed Growth; Herbicides; Weed Management Practices; Nodulation